2022
DOI: 10.1155/2022/5872889
|View full text |Cite
|
Sign up to set email alerts
|

Study on Movement Law of High-Position Thick and Hard Roof and Mine Earthquake Control by Ground Fracturing Technology

Abstract: The field monitoring data showed that the fracture of high-position thick and hard roof (THR) was the main reason for the frequent occurrence of high-energy mine earthquake events ( magnitude > 2.0 ) in the no. 6 mining district of Dongtan coal mine. In order to study the fracture characteristics of high-level THR and seek a reasonable and effective control method, taking the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Gao et al [14] established the mechanical model of the strong-soft-strong structure, and they concluded that the weak rock layer can provide good energy absorption to protect the roadway. Horizontal well fracturing, which is applied to the hard rock layer above the coal seam, can effectively reduce the occurrence of high-energy mining-induced seismic events by facilitating the fracture of the hard rock layer, decreasing the integrity of the rock mass, and increasing the quantity and distribution range of internal fractures within the rock mass [15][16][17][18][19]. After ground hydraulic fracturing was performed, the fractured strata experienced stress relief, resulting in reduced rock strength.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [14] established the mechanical model of the strong-soft-strong structure, and they concluded that the weak rock layer can provide good energy absorption to protect the roadway. Horizontal well fracturing, which is applied to the hard rock layer above the coal seam, can effectively reduce the occurrence of high-energy mining-induced seismic events by facilitating the fracture of the hard rock layer, decreasing the integrity of the rock mass, and increasing the quantity and distribution range of internal fractures within the rock mass [15][16][17][18][19]. After ground hydraulic fracturing was performed, the fractured strata experienced stress relief, resulting in reduced rock strength.…”
Section: Introductionmentioning
confidence: 99%
“…These tremors, given their proximity to the surface, frequently result in significant vibration on the ground, instigating widespread concern. Currently, coal mines with a high frequency of such far-field strong mine tremors include Hongqinghe (Zhang et al, 2021), Jinjitan, Shilawusu (Yang et al, 2023), Dongtan, Nantun (Guo et al, 2022;Liang et al, 2022), Baodian (Cao et al, 2015;He et al, 2022). Notably, Dongtan, Nantun, and Baodian all fall within the Yanzhou coalfield, positioned near one another, and share similar mining conditions characterized by the presence of substantial, maroon thick sandstone layers above the coal seam, often referred to as the "red layer".…”
mentioning
confidence: 99%